Collegiate athletes' perceptions of the connection between mental health and sport performance: a qualitative investigation - Beebe, K. E.; Petrie, T. A.; Kiefer, H. R.; Slavin, L. E.; Arnold, M. L. (Journal of Clinical Sport Psychology, 2024)
Prevalence of mental health (MH) concerns among young adults is high and continues to increase. As a specific subset of young adults, National Collegiate Athletic Association (NCAA) athletes seem to experience these concerns at a similar or greater prevalence rate than their nonathlete, age-matched peers. Yet, how MH affects sport performance has not been robustly studied, and existing studies have not included the diversity of identities present in the collegiate athlete population. Thus, via online survey, this study explored the beliefs of 249 collegiate athletes representing diverse identities and sports regarding how MH affects sport performance. Regardless of demographic variable, 96.4%-100.0% of participants believed that MH affects sport performance. Three themes were identified: (a) collegiate athletes affirm that MH affects sport performance, (b) collegiate athletes` perceptions of how MH affects sport performance, and (c) collegiate athletes believe that being a collegiate athlete exacerbates their MH concerns. The universality of endorsement and the themes represent novel findings that warrant further exploration of the MH-sport performance connection.